9b+7-1=

Simple and best practice solution for 9b+7-1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9b+7-1= equation:


Simplifying
9b + 7 + -1 = 0

Reorder the terms:
7 + -1 + 9b = 0

Combine like terms: 7 + -1 = 6
6 + 9b = 0

Solving
6 + 9b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 9b = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 9b = 0 + -6
9b = 0 + -6

Combine like terms: 0 + -6 = -6
9b = -6

Divide each side by '9'.
b = -0.6666666667

Simplifying
b = -0.6666666667

You can always share this solution

See similar equations:

| 10x-16=74 | | 1.32g-8=0.58 | | 6(5+7z)= | | 9x+8=71 | | 42=8m-13m | | 2(-x-1)=2x-34 | | 3(x-1)+5=25 | | 5(-7z-6)= | | 49x^2-196=0 | | 5t-0=-3t+7 | | 3(-14+2)=4(5-14) | | -5(n+8)=-98 | | 4g+3g+9g= | | x^2-13x=-30 | | 4(3x-2)=52 | | 5x^2-24x+18=0 | | 3x^2-6x+45=0 | | x^2-13=-30 | | 32+5(8.6)=n | | 5r+r+4r= | | 24=5x+6-2x | | 11r-6r+5r=168 | | 32+5(8.6)= | | 3(-14+2)=4(5-13) | | 3y+10=9 | | 3m-4=2m-13 | | 41+8z=-z^2 | | 8x+12=100 | | b-3+3b=36 | | 3y+7=9 | | 4(y+2)=5(y-5) | | 6x-10=-18x-4 | | 3x^2-15x+45=0 | | 2(-2+x)-1(x-4)=0 | | (x-6)(5x+3)=0 | | 27=y | | (x+3)(6x+7)=0 | | 2y-8=-y+4 | | 6x^2-8x+3=0 | | 0=-5h-2h | | 4h*6h= | | -2+2y=-4 | | 3-4r=10r+10 | | (3m-4n-7)-(8m+n-6)= | | 32+5n=75 | | 2y=4x-3 | | 2+11x=12x-6 | | (3m-4n-7)(8m+n-6)= | | y^2-16x-6y+25=0 | | 3(a-2)=9(a+2) | | 9x-15= | | 3=12-3x | | -7h-4=h+4 | | 62-c=42 | | -3b-2a-4c+5b-8a= | | 4d-8=19 | | 4(x-4)-11x= | | 6c-12=48 | | 25h=20h+15 | | 1-2x=16-5x | | 4y+6=-14 | | 9(6x+3)= | | 7x=11x+16 | | 3x+-7=-8 | | 9a-4a+a-10= |

Equations solver categories